Penyuluhan Bahaya Penggunaan Obat Tradisional Tanpa Resep Selama Kehamilan Terhadap Risiko Abortus - Saputri, Nurul Aini Suria; Insani, Uswatun (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
The background to this activity stems from the high prevalence of over-the-counter use of traditional medicines among pregnant women, particularly in rural areas, without adequate understanding of their side effects on pregnancy. One serious risk of using traditional medicines without a prescription is abortion or miscarriage, which can be caused by the presence of certain active compounds in unstandardized herbal concoctions. The purpose of this community service activity is to increase pregnant women's knowledge about the dangers of using traditional medicines without medical consultation and to educate them about the importance of regular prenatal check-ups through health education. The implementation method for this activity included providing counseling materials, group discussions, case simulations, and evaluation through pre- and post-tests. The activity was conducted on July 15, 2025, in Village Y, District A, and involved 35 participants, consisting of pregnant women and health cadres. The results showed an increase in participants' understanding of the risks of inappropriate use of traditional medicines, with the average post-test score increasing by 61% compared to the pre-test. This activity also succeeded in building collective awareness about the importance of consulting a health professional before consuming traditional concoctions during pregnancy. This outreach activity is expected to be an early intervention that can prevent abortions caused by unsafe traditional medicine practices. Ongoing education and the involvement of community leaders and cadres are crucial strategies in developing safer, evidence-based health behaviors.